A Study For The Potential Of Ammonia-Wood Charcoal Adsorption Refrigeration System - Wong , Chee Khoon (2012)
Adsorption systems have gained popularity over vapour compression system due to their being environmentally benign, having zero ozone depletion potential and zero global warming potential. Despite much research on the adsorption and desorption of ammonia on activated carbon, relatively few reports were found for wood charcoal. In this study wood charcoal, obtained locally, was crushed and sieved into three particle sizes for study. Particles sized 1.18 to 3.35 mm yielded the highest specific surface area which of 155.37lm2 g-1 with specific volume of 0.1309lcm3 g-1 and an average pore diameter of 2.503lnm.